Comparing the Oral Health Status of Diabetic and Non-Diabetic Children from Puerto Rico: a Case-control Pilot Study - López del Valle, Lydia M.; Ocasio-López, Carlos (Puerto Rico Health Sciences Journal, 2011)
Objective: Children with type 1 diabetes have infrequently been the subjects of studies examining oral health status (caries and gingival diseases); in addition, no study of this type has ever been on Puerto Rican children. The purpose of this study was to evaluate the oral health status of Puerto Rican children (ranging in age from 6 to 12 years) either with or without type 1 diabetes and compare the two groups with regard to that status. Methods: This was a matched case-control study. A convenience sample of 25 children with type 1 diabetes (cases) and 25 non-diabetic children (controls), all ranging in age from 6 to 12 years and matched by age and gender, was evaluated by a calibrated dentist for caries, bleeding on probing, and plaque and calculus indexes. A sample of saliva was taken from each subject and analyzed to determine Streptococcus mutans and Lactobacillus counts. Descriptive statistics, chi-square test, and t-test were used to describe and assess the data. Results: We used the caries index to evaluate the teeth of the children participating in our study; we found significant differences in the number of lesions in the permanent teeth of diabetic children compared to the number found in the permanent teeth of non-diabetic children (1.43 and 0.56, respectively; p = 0.05). The mean number of sites of bleeding on probing for diabetic children was 23.9; for non-diabetic children it was 4.2. Diabetic children had more plaque than did the control children (plaque index = 2.5 vs. 0.8; p = 0.007) and more bleeding on probing (p = 0.001). High levels of glycosylated hemoglobin in diabetic children were statistically significantly associated with a greater number of sites with bleeding on probing. Conclusion: Diabetic children are at higher risk for caries and gum disease than are non-diabetic children.